Relationship among macroeconomic factors and stock prices: cointegration approach from the Indian stock market - Sarika Keswani; Veerma Puri; Rimjhim Jha (Cogent Economics & Finance, 2024)
The performance of a stock market is intrinsically linked to the broader financial and economic landscape of a country. Stock prices, as integral indicators, not only mirror the financial health and collective economic circumstances of a nation but also serve as crucial barometers of tangible financial activities. This research paper aims to undertake a comprehensive exploration of the intricate relationship between specific macroeconomic determinants and the stock market within the context of India. Moreover, this study conducts an exhaustive analysis to assess the relative significance of these variables and their contributions to the predictive capacity of stock prices. This investigation harnesses a dataset consisting of monthly observations of the chosen macroeconomic variables. The outcomes of the cointegration analysis illuminate a robust and statistically significant long-term association between Indian stock prices and the selected macroeconomic factors. The results of the cointegration test affirm a lasting nexus between stock returns and crucial economic indicators, namely Gross Domestic Product (GDP), disposable income, and the participation of Foreign Institutional Investors (FII) in the market. Furthermore, this study underscores the enduring negative relationship between stock returns and factors, such as interest rates, government policies, exchange rates, and inflation. These findings provide valuable insights into the interplay between the stock market and macroeconomic forces in the Indian context. This study comprehensively examines the intricate relationship between macroeconomic variables and the Indian stock market from 2009 to 2019. Utilizing a monthly dataset and rigorous statistical techniques, such as cointegration analysis and the VECM Granger causality test, the research elucidates a significant long-term relationship between macroeconomic variables like GDP, disposable income, and Foreign Institutional Investor (FII) participation, and Indian stock prices. The empirical results reveal a negative correlation with interest rates, government policies, exchange rates, and inflation, and a positive long-term correlation with GDP, disposable income, and FII involvement. The cointegration tests substantiate these findings, reaffirming the enduring nature of these relationships. Furthermore, the VECM Granger causality test highlights the substantial impact of changes in these macroeconomic variables on short-term stock price fluctuations. The study's conclusions shed new light on the dynamic relationship between macroeconomic factors and the stock market in India. By identifying the predictive capacity of key economic indicators on stock price movements, this research contributes to more informed and strategic decision-making for policymakers, investors, and economists, thereby enhancing the efficacy of economic planning and investment strategies.
Keywords: E2; E4; E6; 330; Disposable income; exchange rates; economic growth (GDP); FII; government policies; interest rate; inflation